CATEGORY SHIFTS IN TRANSLATING ENGLISH COMPLEX NOUN PHRASE INTO INDONESIAN IN OPRAH - Prawita, Ni Ketut Riska Dewi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
This paper aims at analyzing the types of category shifts of complex noun phrase and identifying the types of loss and gain of information. The data was taken from the biography entitled Oprah as the source language, as well as its Indonesian version that has the same title, Oprah, as the target language. It was analyzed by applying the qualitative descriptive method. The categorization of the complex noun phrase was explained by using the tree diagrams. There are two theories applied in this paper, they are the theory proposed by Catford (1965) to analyze the types of category shifts and the theory proposed by Nida (1975) to describe the types of loss and gain of information found in the translation of Oprah.The result of this analysis in the paper indicates that complex noun phrase in English can be translated into Indonesian in two forms, they are complex noun phrase and non-complex noun phrase. Structure shifts and intra system shifts consist of complex noun phrase in translation. Meanwhile, class shifts and unit shifts consist of non complex noun phrase in the translation. Moreover, the occurence of loss and gain of information can not be avoided in the translation.
Keywords: category shifts, complex noun phrase, tree diagrams, and “Oprah”